Pembuatan Headpiece dengan Kombinasi Clay untuk Peluang Berwirausaha - Wanda Vera Lestari; Agus Susanti; Sofia Daniati (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Headpiece is an accessory worn on the head to beautify the appearance. The author uses observation, literature, experiments, documentation, and questionnaire methods. The author conducted a qualitative descriptive data analysis by presenting it in the form of a narrative using words or sentences. The author conducted experiments with stages, namely preparing materials and tools, forming flower patterns, arranging flower petals, arranging flowers and beads, applying glitter, applying resin, drying resin, arranging flowers and beads on a wire headband. The author offers a price of IDR 57,500 per headpiece, which is a relatively cheaper price compared to headpieces made of beaded flowers. Product validation was tested through sensory tests on 3 expert validators and obtained a total value of 57, which is included in the very feasible category, while the level of preference according to 30 respondents for clay headpiece products received a value of 119-150 which is included in the very preferred category. Based on the results of research and experiments on making headpieces from a combination of clay for entrepreneurial opportunities, it is hoped that in the future there will be more variations in headpiece types, improve the quality of headpieces, increase the variety of flower shapes and marketing strategies.